Genome-wide analysis of Streptococcus pyogenes associated with pharyngitis and skin infections. (c2015) - Ibrahim, Joe P. (2016)
Streptococcus pyogenes is a very important human pathogen, commonly isolated from the skin or throat of individuals. Belonging to the Group A Streptococcus (GAS), S. pyogenes is responsible for a myriad of infections both benign and life-threatening. Superficial infections by the microorganism are manifested through pharyngitis, tonsillitis, and localized skin infections, while the more invasive and often lethal infections include sepsis, streptococcal toxic shock syndrome (STSS), and necrotizing fasciitis. Various studies involving typing and molecular characterization of S. pyogenes have been performed to date; however next-generation sequencing (NGS) studies are still a handful. In this study, the genomes of nine S. pyogenes isolates associated with pharyngitis and skin infection were sequenced using the NGS approach, and subsequently analyzed for the presence of virulence genes, resistance elements, prophages, genomic recombination, and other genome wide features. All of the sequenced isolates were found to carry an array of genes encoding fibronectin binding proteins, exotoxin cytolysins, and immunoglobulin degrading enzymes. Additionally, all of the isolates encoded the characteristic streptococcal C5a peptidase, with a very high sequence homology observed between the individual isolates. The chromosomally encoded superantigens SpeG and SmeZ were naturally found in all the isolates, whereas differences were seen when studying phage-encoded ones. All of the genomes housed the SpeB while SpeK and SSA were found in two thirds and one third of the genomes respectively. Of the generated superantigen profiles, the two most common were SpeBGKZ and SpeBGJZ both of which are mostly associated with sepsis and cellulitis. Interestingly, one isolate linked to emm1 serotype, had a superantigen profile associated with glomerulonephritis. Antimicrobial resistance determinants were identified to be mostly against three antimicrobial agents namely being: macrolide, fluoroquinolone and tetracycline. Macrolide resistance ABC efflux permeases were found in all of the sequenced genomes, fluoroquinolone resistance was seen in all of the isolates as well mainly through mutations in the DNA gyrase A and B subunits. Only two of the isolates however, showed elements of tetracycline resistance suggesting a multi-resistant European clone lineage. Numerous phage and prophage elements were also detected on the streptococcal genomes, which is a characteristic feature of the species. The presence of such mobile elements explains the extensive genomic rearrangements seen in S. pyogenes. Large lineage diversity was also observed amongst the isolates which can also be attributed to genomic recombination events, mediated through phage integration instances or other horizontal gene transfer mechanisms. Phylogenetic tree construction revealed a strong link between our isolates and global clones causing invasive diseases. This study, that to our knowledge is the first of its kind in the region, elucidates the importance of the NGS approach as a tool to unlock different characteristics of bacterial genomes. Through this work, clinically relevant features of the S. pyogenes isolates, in addition to genome wide determinants were successfully detected, simultaneously. Studies similar to this one may be the cornerstone of both clinical and research oriented studies thus improving our knowledge and treatment approaches against such important human pathogens including S. pyogenes.